Reaction-Diffusion Manifolds including differential diffusion applied to methane/air combustion in strong extinction regimes. Issue 3 (16th April 2022) - Breda, Paola; Yu, Chunkan; Maas, Ulrich; Pfitzner, Michael
Abstract : Detailed chemistry simulations of turbulent reacting flows involving combustion of hydrocarbons can easily exceed the available computational resources, depending on the dimensions of the chemical system. Previous work of the authors showed how the combination of the Eulerian Stochastic Fields (ESF) model with tabulated chemistry based on 2-dimensional Reaction-Diffusion Manifolds (REDIM) provided a significant computational speed-up, compared to the finite rate ESF solver. In this work, the behaviour for flame F, featuring a strong degree of extinction, is further investigated. A comparison is performed for 2D and 3D databases, both using simplified and detailed transport, where the scalar dissipation rate is included as the third table parameter. The results show that the upstream sections are well captured by the REDIM built for detailed transport, while the downstream sections are better captured by the simplified transport database. While a 3D-REDIM based on simplified transport seems to be necessary to capture the extinction events, a 2D-REDIM with differential diffusion already provides satisfactory results. Overall, the use of a 3D-REDIM with differential diffusion better describes the global behaviour of flame F.